2017
DOI: 10.5195/jmla.2017.104
|View full text |Cite
|
Sign up to set email alerts
|

Meeting at the crossroads: collaboration between information technology departments and health sciences libraries

Abstract: ObjectiveThe purposes of this survey were to determine the nature and extent of collaboration between health sciences libraries and their information technology (IT) departments, to identify strengths and issues connected to this relationship, and to provide examples demonstrating exceptional collaborative success.MethodsA fourteen-question survey was sent to a broad selection of health care and academic libraries through a variety of email discussion lists and was limited to one response per institution. Conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This supported Gentry and Marone's finding that regular meetings of medical library staff and IT staff fostered solutions to technical issues and facilitated access to library electronic resources for the hospital staff [21]. Likewise, a survey of health sciences libraries, including academic and hospital libraries, found that respondents attributed successful collaborations with IT to "open communication," an understanding of the expertise of staff in each department, and a "collegial environment" [26].…”
Section: Discussionmentioning
confidence: 58%
“…This supported Gentry and Marone's finding that regular meetings of medical library staff and IT staff fostered solutions to technical issues and facilitated access to library electronic resources for the hospital staff [21]. Likewise, a survey of health sciences libraries, including academic and hospital libraries, found that respondents attributed successful collaborations with IT to "open communication," an understanding of the expertise of staff in each department, and a "collegial environment" [26].…”
Section: Discussionmentioning
confidence: 58%
“…Specialized software and tools are needed by the library to maximize ease of access for the library’s clientele (link resolvers, database management systems, as examples). The library/information service works in partnership with the institutional IT department in order to purchase, install and maintain library software and technology [ 79 ].…”
Section: Standard Eight: Technologymentioning
confidence: 99%
“…However, due to the limitation of campus network security, the consensus was a temporary solution to embed the Word Press Accessibility Helper Plugin, which provided a more accessible alternative. King et al (2017) clearly explain that "the IT department act as gatekeepers for many library activities, hence meeting users' demands for easy-to-access, digital services requires cooperation between" stakeholders critical to building efficient and friendly working relationships. In addition, website accessibility is an essential resource in many aspects of life, literature, and society.…”
Section: Web Accessibilitymentioning
confidence: 99%